Evaluation of a course for simulation instructors at a Peruvian university - Shibao Miyasato, Hector; Armijo-Rivera, Soledad; Casas Bueno, Fresia; Sandoval Barrantes, Ana Maria; Delgado Guevara, Ximena; Gutiérrez Díaz, Miguel; Valdivia López, Stefany; Villalobos Ulfe, Roberto; Machuca-Contreras3 , Felipe (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: medical education is constantly evolving to respond to the demands of the clinical and social context, and it is of vital importance to design and implement training programs according to the needs of each educational institution for training and improvement of educational services.Objective: to evaluate the satisfaction of the course carried out by the UPCH simulation center using the Kirkpatrick model.Methods: a survey was used at the end of the course and another one after 1 month. All responses were recorded using a Google Forms format.Results: in the General Satisfaction section, 66 % of the participants responded, "Very satisfied".  In the General Evaluation section, regarding the organization of the course, the most voted answer was "very well" with 52 %. Regarding the pre-course bibliography, 54 % of the participants thought it was "Very good". Finally, regarding the facilities where the course was held, 62 % of the respondents indicated that it was "Excellent", 36 % of the participants mentioned the ECOE Module as the part of the course they found most useful.Conclusion: it is recommended to periodically include the clinical simulation teaching methodology course as a requirement for simulation trainer training as well as to continue to implement surveys in order to make changes and improvements through participant feedback.